A Methods engineering study on Razon's Palabok and Halo-Halo - Gonzales, Dian (College of Engineering, 2005)
Teresita R. Razon's Palabok and Halo-halo is basically a food service company. Their specialties, palabok and halo-halo, and merienda items such as burgers, sandwiches, and French fries are served the whole day. Pasalubong items are also sold at the counter or upon ordering. They also accept large orders and take-outs. This study focused on determining major problems as well as the minor ones that hinder the company in reaching their optimal goal-customer satisfaction and high profit. A number of steps were done to fully recognize such circumstances and come up with recommendations that will attract customers that will lead to higher profit. Methods documentation and analysis is done on actual plant visits, employing various tools learned in the Methods Engineering class. The study addressed problems, namely : no definite work assignments, irregular driver's schedule, delay in service during peak hours, fatigue experienced due to grinding of ice, improper issuing of bills, improper storing of raw materials and ingredients, inefficient layout, unsystematic standard operating procedures. It is the task of the group to come up with possible solutions to the aforementioned problems. The proposed solutions are subject for implementation. The group is also tasked to at least try to plant the implementation. In doing so, the group come up with an implementation plan and implementation strategy. Application of the tools learned in methods analysis class is very much of use in this project study. The group would not be able to come up with all that is inside this paper without the thorough understanding of various tools of Methods Engineering.